From capitalist-urbanisation as politics-of-refuge to planning as planetary-politics-of-care - Tulumello, Simone (2019)
Dedicating a PTP Interface to spaces of refuge, migration and border enforcement is a very timely decision. The six pieces collected here set out a truly global picture of the nexus of human mobility, politics of citizenship and planning amid turbulent processes of capitalist urbanisation – or, to put it with Neil Brenner and Christian Schmid, ‘planetary’ urbanisation. I particularly appreciate the way the contributors were able to open up the ‘immigration and refugee crisis’. For one, the authors indirectly expose the pathetic cry of Western politicians and media for the tiny fraction of the world refugee population their wealthy countries have to deal with. More importantly, the six pieces also provide a clear picture of the real ‘crises’ at stake: crises of housing, urban development, dispossession and extraction, imperialist war – the latest, and most hideous, crisis of capitalism-as-urbanisation (cf. Rossi, 2017), in short.